2014
DOI: 10.1080/14786419.2014.945174
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activities of a new benzamide from endophyticStreptomycessp. YIM 67086

Abstract: A new benzamide (1) and four known compounds (2-5) were isolated from endophytic Streptomyces YIM67086, and their structures were determined as 2-amino-3,4-dihydroxy-5-methoxybenzamide (1), 4-hydroxy-3-methoxybenzoic acid (2), phenylacetic acid (3), N-acetyltyramine (4) and p-hydroxytruxinic acid (5). Compound 5 was first found in the microorganism. The antimicrobial activities of compounds 1-5 and antioxidant activity of compound 1 were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…Streptomyces species are gram-positive filamentous bacteria, which can grow in various ecosystems, including sea sponges (Han et al 2009), soil (Nguyen et al 2015), animal faeces (Wang et al 2014) and termites (Zhang et al 2013). They are able to produce both secondary metabolites (Wang et al 2013;Zhang et al 2013) and hydrolytic enzymes (Karthik et al 2015;Nagpure and Gupta 2013) or potentially novel anti-microbial compounds (Yang et al 2015;Yekkour et al 2015;Shakeel et al 2018). Some compounds have been shown to inhibit spore germination (Wang et al 2013;Zhang et al 2013) and mycelial growth of spoilage fungi (Nguyen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Streptomyces species are gram-positive filamentous bacteria, which can grow in various ecosystems, including sea sponges (Han et al 2009), soil (Nguyen et al 2015), animal faeces (Wang et al 2014) and termites (Zhang et al 2013). They are able to produce both secondary metabolites (Wang et al 2013;Zhang et al 2013) and hydrolytic enzymes (Karthik et al 2015;Nagpure and Gupta 2013) or potentially novel anti-microbial compounds (Yang et al 2015;Yekkour et al 2015;Shakeel et al 2018). Some compounds have been shown to inhibit spore germination (Wang et al 2013;Zhang et al 2013) and mycelial growth of spoilage fungi (Nguyen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms can also induce the production or accumulation of plant metabolites that can improve tolerance of plants to stresses [4][5][6]. Some studies have shown that microorganisms can mediate the interaction between host plants and pathogens by producing antimicrobial compounds and antioxidants or inducing systemic resistance [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary metabolites (1)(2)(3)(4)(5)(6) of Streptomyces played an important role in natural products which have attracted great attention of researchers due to their complicated structures and potential biological activities. Previously reported chemical investigations of the genus Streptomyces include the antifungal hygrolidin (7), cytotoxic elmonin (8), antibacterial angumycinone C (9) and antitumour streptonoate (10).…”
Section: Introductionmentioning
confidence: 99%